Hermenéutica de los Componentes Ideológicos que intervienen en el Proceso Educativo Ecuatoriano en el Siglo XXI - Molina Altamirano, Janneth Rocío (2015)
The way how we see the world and our way of living itself, it involves us to own components of an ideology. Louis Althusser shows us a theory of a nearby ideology to place us in front of the reality and to distinguish how the ideology is broadcasted by the State Ideological Structures. From this point of view, education becomes one of the most important institutions of monitoring of the State. The analysis of the Ecuadorian Educational Law of the 21st century, demonstrates us an idea of the educational reality, showing us that the state has assumed education as a part of its political structure. So, the challenge of education is nowadays to offer the tools to develop the critical thought towards the imaginary and symbolic of the students, in order to encourage the transformation of the society from the dialog, awareness and agreement.